The effect of B‐doping on the electrical conductivity of polymer‐derived Si(B)OC ceramics. Issue 10 (15th June 2017) - Sorarù, Gian Domenico; Kacha, Getnet; Campostrini, Renzo; Ponzoni, Andrea; Donarelli, Maurizio; Kumar, Arun; Mariotto, Gino
Abstract: In this work the room temperature electrical conductivity of Si(B)OC glasses made via polymer pyrolysis at 1200°C and 1400°C (maximum temperature) and having different amount of boron was measured. When B content is increased from zero (pure SiOC glass) up to B/Si=0.5 the electrical conductivity increases in 2 orders of magnitude from 4.09±0.64×10 −5 up to 2.93±1.91×10 −3 with a corresponding decrease in the activation energy from about 1.08 to 0.51 eV. This results shows for the first time that the electrical conductivity of Si‐based polymer‐derived ceramics can be controlled by the amount of the doping element. The structure of the Si(B)OC glasses has been studied with different techniques including FT‐IR, XRD and Raman spectroscopy. The Raman study indicates that B partially substitutes C into the sp 2 C planes of the free carbon phase forming trigonal BC3 units. Accordingly, the evolution of the electrical properties with the B content has been correlated with the corresponding structural evolution and a hypothesis is presented to rationalize the role of boron on the electrical conductivity of SiOBC glasses.